IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER PADA TOKO HAEKAL KELURAHAN ARCAWINAGUN PURWOKERTO TIMUR - Suyono, Eko; Rusmana, Oman; Arintoko, Arintoko (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Traditional stores continue to experience the following weaknesses: unclear organizational structure and work division, lack of recording and reporting financial transactions, and imperfect accounting information systems. This PKM implementation is taking place at the Haekal Shop located at Jl. Margo Mulyo No. 2RT 008 RW 008, Arcawinangun, East Purwokerto, and is expected to be completed by the end of October 2023. This PKM aims to implement an accounting information system for the management of financial transactions in traditional partner stores. The output of the 2014 National Strategic Research, which collects data qualitatively through in-depth interviews and Focus Group Discussions, is the product. The majority of traditional shops in Banyumas still manage their financial transactions manually, while others have already adopted basic computer systems, according to the findings of this study. In general, these traditional businesses have not instituted accounting recording and reporting in accordance with Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). In 2014, research based on these findings developed an appropriate model for a retail or shop financial transaction management system. Using Toko Haekal as a partner, this PKM activity is presently in the stage of implementing the accounting information system model resulting from this research in the form of a manual-based and computer-based accounting system.